Kesiapan dan Hambatan Guru dalam Mengimplementasikan Kurikulum Merdeka di Sekolah Dasar - Ardhani, Kusuma; Tisngati, Urip; Sugiyono (PGSD STKIP PGRI Pacitan, 2023)
This study aims to describe: (1) the implementation of the independent curriculum, (2) the readiness of teachers in implementing the independent curriculum, (3) the obstacles of teachers in implementing the independent curriculum in SD Negeri Ponggok. This research uses qualitative research methods using a descriptive approach. The subjects in this study were principals and teachers of SD Negeri Ponggok. Data collection techniques include observation, interviews, and documentation. Data analysis using qualitative descriptive techniques. The results obtained in this study are: 1) The implementation of the independent curriculum in learning is categorized as very good, which includes learning preparation, learning implementation, and learning assessment; 2) The readiness of SD Negeri Ponggok teachers in the implementation of the independent curriculum is categorized as very good in preparation, implementation, and learning assessment and of the three characteristics of the independent curriculum on the observation sheet, two of them are met; 3) The obstacles experienced by teachers of SD Negeri Ponggok in implementing the independent curriculum, namely the difficulty of changing the old teaching method and the application of differentiated learning that has not been maximized.